Error analysis of present simple tense in the interlanguage of adult Arab English language learners - Muftah, Muneera; Rafik-Galea, Shameem (Canadian Center of Science and Education, 2013)
The present study analyses errors on present simple tense among adult Arab English language learners. It focuses on the error on 3sg –s (the third person singular present tense agreement morpheme –s). The learners are undergraduate adult Arabic speakers learning English as a foreign language. The study gathered data from two types of instruments: a grammaticality judgment task (GJT comprising both grammatical and ungrammatical items and an elicited written production task (EWPT). Both tasks were designed to test the learners’ underlying knowledge of present simple tense morphology in the Interlanguage (ILG) of adult Arab English language learners. The GJT comprised 12 grammatically/correctly inflected items, 6 omission items (OI) and 6 wrongly/incorrectly inflected items (WI). The findings suggest that adult Arab English language learners seem to have difficulty mastering the use of the 3sg –s due to first language (L1) interference. The findings of this study have pedagogical implications for English as a foreign language classroom teaching practice as well as for second language teachers and researchers. The most frequent error types produced by the Learners are omission, phonological similarity, incorrect suffixation and substitution.